Pengaruh Pengetahuan Pajak Dalam Wajib Pajak terhadap Kegiatan Usaha - Hidayat, Imam; Damayanti, Alfina Ayu (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Income is a tax object. Income tax imposed on tax subjects on income received or accrued in a tax year. Income tax is classified as tax subjectivity, namely a tax that considers the personal condition of the taxpayer as the main factor of tax imposition. Defining a taxpayer that reflects the ability to pay taxes, namely the strength of the burden is taken into account as the main basis in determining how much tax is charged to him. In accordance with the Tax Law No. 28 of 2007 article 2. Taxpayers who have met the subjective and subjective requirements in accordance with the provisions of the applicable laws and regulations, must register themselves at the office of the Director General of Taxes whose working area covers the residence or domicile of the Taxpayer. For Indonesia, taxes are an important source of state revenue. Income tax is a type of tax collected at the national level so that it can be included in the tax center group. With the issuance of this law, the government has provided many conveniences for taxpayers to provide confidence and freedom in calculating the tax payable against revenue. Keywords: Tax; Compliance; Business Activities